Ivan Franko and his community - Hrytsak, IAroslav (Biblioteka ukraïnoznavstva., 2018)
This book brings us to the very core of the debates about nations and nationalism. It presents a microhistory of Ivan Franko (1856-1916), a prolific writer and political activist, who was an indisputable leader in forging a modern Ukrainian identity in the late Habsburg Galicia.